BILATERAL INVESTMENT TREATIES SEBAGAI INSTRUMEN NEGARA DALAM MEMBERIKAN PERLINDUNGAN INVESTASI TERHADAP ASING - Suwardi, Suwardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Interdependence between countries has pioneered various forms of international cooperation. Bilateral Investment Treaties / Agreements for the Promotion and Protection of Investment are one of the bilateral agreements between two countries that are legally binding with the aim of establishing mutual protection and promotion of investment in both countries. With the Investor-State Dispute Settlement, it is hoped that it can provide protection for foreign investors, by providing a dispute resolution forum, one of which is through the International Center for Settlement of Investment Disputes.